Effects of plasma surface treatment on bending strength and modulus of elasticity of beech and poplar plywood - Demirkir, Cenk; Aydin, Ismail; Colak, Semra; Ozturk, Hasan (Maderas. Ciencia y Tecnología, 2017)
This is a study on the effect of plasma treatment with different gases and plasma intensity on the bending strength and modulus of elasticity of plywood manufactured from beech and poplar. Oxygen (O2) and ammonia (NH3) plasma were applied on the veneer sheets; two plasma intensities were applied on the veneers with 150 and 300 W in the plasma chamber during one minute. Phenol formaldehyde resin was applied on one surfaces of each veneer with approx. 160 g/m2. Bending strength and modulus of elasticity were determined according to EN 310.The effects of plasma surface treatment on chemical structure of the panels were determined with FTIR-ATR analysis. Bending strength of all tested panels slightly and partly increased without statistical significance when applying oxygen plasma. The effect of ammonia plasma treatment on bending strength and was determined by the wood species and the plasma intensity, and it was not uniform. Modulus of elasticity of the panels with oxygen plasma treatment showed in most cases improvement, whereas ammonia plasma pretreated veneers caused lower values compared to the control panels.